Inquiry-based Approach in Technical Education - Kožuchová, Mária; Dostál, Jiří (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
The article is based on fundamental social-cognitive theories that are based on a natural way of cognition of the world. The research process itself (the formation of hypotheses and predictions and their subsequent verification, the formation of conclusions that are supported by the facts, generalization) contributes to a modification of preconcepts and the development of the specific cognitive abilities of students. Moreover, it is also a matter of the development of the willingness to cooperate, development of enthusiasm and interest in exploring of the world around them. The aim of the paper is to clarify the theoretical bases of the inquiry-based approach in technical education and didactic specifications of anchoring of the sequence of the educational steps in the technical education. In the empirical part, the article is focused on teachers’ competences to the realization of the inquiry-based instruction.
Keywords: technical education; inquiry-based instruction; teachers´ competences